Surface hydrophilization of highly porous poly(ether imide) microparticles by covalent attachment of poly(vinyl pyrrolidone). (1st December 2020) - Kratz, Karl; Heuchel, Matthias; Weigel, Thomas; Lendlein, Andreas
Abstract: The realization of a permanent surface hydrophilization for highly porous microparticles designed for removing uremic toxins from the blood of renal failure patients, without altering their complex pore structure, represents a challenging task. Here we report on the hydrophilic surface functionalization of porous poly (ether imide) (PEI) microparticles, having a mean diameter of 226 ± 14 μm, a porosity of around 84 ± 2% with a mean pore diameter of 230 ± 40 nm, by covalent attachment of amino-terminated poly (vinyl pyrrolidone) (PVP–NH2 ) with a number average molecular weight of M n = 5400 g mol −1 . X-ray photoelectron spectroscopy confirmed a successful surface modification by a change in the surface chemistry, in particular the N/C ratio. The PEI-PVP particles exhibited an advancing water contact angle of θ adv = 75° ± 5° as determined in environmental scanning electron microscopy microwetting experiments. The obtained results from mercury intrusion porosimetry and nitrogen adsorption experiments documented the preservation of the porous structure of the particles in the cause of the modification, which could be visualized by electron microscopy. The presented approach enables a covalent hydrophilization of porous particles while preserving their nanoporous morphology. Graphical abstract: Image 1 Highlights: Preserving the structure of poly (ether imide) particles during surface modification. Hydrophilization by covalently attaching amino-terminated poly (vinyl pyrrolidone). Functionalized particles form inter-particle capillary water bridges.